Development of FAST (Fun and Smart Testing with Kahoot) Interactive Gamification Media to Improve Students' Understanding of Human Digestive System Materials in Grade V Elementary School - Deulis Ruswati; Endin Mujahidin; Rudi Hartono (CV. Media Inti Teknologi, 2025)
Background of study: Many elementary school students have difficulty understanding abstract science concepts, such as the human digestive system. Monotonous conventional learning methods are considered less able to attract students' attention.Aims and scope of paper: This study aims to develop FAST (Fun and Smart Testing with Kahoot) interactive gamification media to improve students' understanding of the human digestive system material.Methods: The research used the Borg & Gall development model synergized with the ADDIE model. The subjects of the study were 30 students in grade V of Ciherang State Elementary School, Sukabumi. Data collection techniques include observation, interviews, questionnaires, as well as pretest and posttest tests.Results: The development and implementation of FAST interactive gamification media had a significant positive impact. Quantitatively, there was a substantial improvement in student learning outcomes; the average pre-test score of 47 rose to 91 in the post-test. An N-Gain analysis result of 0.82 indicated very high effectiveness in improving learning outcomes. The FAST media also underwent validation by learning design, media, and material experts, receiving very high feasibility scores: 94.4% (design experts), 96% (media experts), and 96.8% (material experts). Responses from both students and teachers were overwhelmingly positive. Students reported feeling more engaged, motivated, and enthusiastic. Teachers found the media helpful in explaining abstract concepts, facilitating direct learning evaluation, and creating a more lively classroom atmosphere, praising Kahoot! for its accessibility and flexibility.Conclusion: FAST interactive gamification media is effective in increasing students' understanding and motivation to learn about human digestive system material.